Responses to climate change adaptation messages: A focus group study on the potential for public engagement with climate adaptation - Perälä, Annu (Sciendo, 2025)
As climate change accelerates, effective communication about climate change adaptation is urgently needed to inform and engage communities concerning proactive measures. In this article, I examine public engagement with climate change adaptation through the lens of message interpretation. Six online focus groups, including working-aged men and women (n = 30), were conducted in Finland in 2024, and the data were analysed using qualitative content analysis. The results suggest that the public demonstrates a cognitive capacity to engage with adaptation, even though many individuals in the study were unfamiliar with the specific term. Consequently, three main emotional responses to adaptation communication were identified, each carrying its own implications for public engagement. First, a supportive view of adaptation as a realistic and sensible strategy aligns with engagement. In contrast, a more critical perspective that considers adaptation as submissive and an incomplete response to climate change may hinder engagement. Lastly, a dismissive view rooted in low-risk perception also obstructs engagement by undermining the rationale for adaptation.
Keywords: climate change adaptation; climate communication; adaptation communication; content analysis; focus groups; Communication Studies; Viestintätieteet